Development of shrimp (Peneaus monodon) head powder - Angara, Maria Luisa; De Leon, Son. (1978)
Experiments were conducted to standardize the procedure for cabinet-dehydration of shrimp head powder and to determine the crude fiber content of this product. There were two phases in the study, Phase I dealt on the standardization of procedure of cabinet-dehydrated shrimp head power by choosing the optimum time and temperature for the dehydration process. In this phase, three different temperatures (140°F, 160°F, and 108°F) were studied. Results of both the objective tests (moisture content, rehydration ratio, and percentage yield) and the subjective tests revealed that drying at 140°F gave a shrimp head powder of better appearance, odor and flavor than those dried at 160°F and 180°F. The finished product was light pink, with a characteristic shrimp odor and flavor. It was rated as "likely moderately" by the panelists. Phase II was on the determination of crude fiber of the shrimp head powder. Results obtained indicate that shrimp head powder has a crude fiber content of
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Sh